Origin of post-ictal and post-anesthesia adverse effects and possibly of SUDEP. (June 2021) - Rabinovitch, A.; Thieberger, R.; Aviram, I.; Biton, Y.; Braunstein, D.
Abstract: The origin of post-ictal malfunctions is debatable. We want to propose a novel idea of a cause of these adverse results occurring following epileptic seizures and anesthesia. Previously we have put forward the idea that epileptic seizures termination is caused by the function of the glymphatic system in the brain. A new measurement shows that this system can be much faster than what was estimated before. Moreover, the method enabling this speeding was actually measured in brains of epilepsy subjects. So, the main objection to our model is relegated. As a possible consequence of the glymphatic process, there can be an excess cleaning of the brain's interstitial fluid. We discuss possible adverse results of this process. This over-cleaning (that can, to a lower extent, occur also during anesthesia) which results post-ictally from the previous overexpression of fluid materials by the neurons during their seizure operation, can reduce ingredients essential for regular neuronal functioning, thereby leading to function reduction and EEG suppression which last until those materials are replenished. We argue that this ingredients' scarcity is the cause of post-ictal generalized EEG suppression (PGES), of post-ictal immobility (PI) and possibly of Sudden Unexpected Death in Epilepsy Patients (SUDEP). Similarly, such cleaning can lead to morbidity and even mortality problems following anesthesia. If our assumption is correct, this understanding of the process of the problems' origin can lead to a method to remedy them by judicial supplement of the lost materials.